Investigating the Relationship between Green Supply Chain Management and Organizational Performance: An Empirical Study from Bangladeshi Perspective - Rahman, Md. Siddikur; Karim, Mohammad Maksudul; Arif, Ishtiaque (International Journal of Supply Chain Management, 2021)
Despite widespread agreement on the significance of organizational performance, little attention has been devoted to investigating its determinants in the context of manufacturing organizations in Bangladesh. As a result, the purpose of this research is to determine the effect of green supply chain management on organizational performance in the manufacturing companies of Bangladesh. A total of 211 respondents from the Bangladeshi manufacturing industry, including supply chain supervisors, managers, and directors, were gathered for this study. Using two independent variables, including green innovation and green process, we were able to assess green supply chain practices, while organizational performance was evaluated using two dependent variables, including environmental performance and financial performance. The SPSS (Statistical Package for Social Sciences) 24.0 program was used to gather demographic information of the respondents, and Smart PLS (version 3.3.3) was utilized to test the research hypotheses. The findings showed that there is a statistically significant positive connection between GSCM and organizational performance. The results of the research have certain implications for practitioners, which are discussed further in the paper. In addition, we addressed research constraints as well as potential study topics for the future.